Developing Algebra-Based Test Items for Measuring Students’ Mathematical Literacy - Handayani Budi Utami (EduMa: Mathematics education learning and teaching, 2025)
This study aims to develop valid and reliable algebra questions to assess students' mathematical literacy skills. Mathematical literacy is a key indicator in international assessments such as PISA, which emphasizes students' ability to apply mathematical concepts in real-world contexts. The research method used was development research (R&D) employing the 4D model: Define, Design, Develop, and Disseminate (implemented until the Develop stage). The instrument was constructed based on mathematical literacy indicators and validated through expert judgment using Aiken’s V. Empirical validation was conducted using Pearson Product Moment correlation and the reliability was tested using Cronbach’s Alpha. The results showed that all question items had correlation coefficients ranging from 0.513 to 0.836, exceeding the critical value of r (0.221), indicating good construct validity. The reliability test yielded a Cronbach’s Alpha of 0.712, suggesting strong internal consistency. These findings confirm that the developed algebra questions can be effectively used as an instrument to assess students’ mathematical literacy skills in a valid and reliable manner.